Investigation and mitigation of premature bearing degradation in motor drive system - Fan, Fei (2020)
Pulse width modulated (PWM) variable frequency drives (VFDs) are commonly adopted in modern control of electro-mechanical drive systems. The use of insulated-gate bipolar transistor (IGBT) and higher switching frequencies has improved the efficiency of the motor drive systems significantly but they also cause high frequency common-mode (CM) currents in the motor bearings. Hence, new drive installations failed prematurely within months, which resulted in unnecessary downtime. Mitigation techniques such as CM filter and motor shaft grounding ring are possible solutions to prevent this kind of premature failure. In this paper, using a 5.5 kW motor drive system as a case study, the cause of bearing degradation is investigated and the various mitigation techniques are carefully evaluated.